2001
DOI: 10.1099/0022-1317-50-2-152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-chain carbohydrates on human intestinal bifidobacteria and Escherichia coli in vitro

Abstract: Plate counts and small subunit (SSU) rRNA abundance were used to study the effects of fructo-oligosaccharides (FOS), fructose, or galacto-oligosaccharides (GOS) on bi®dobac-terial populations in human faecal microbiotas. The bacteria were grown in pHcontrolled anaerobic fermentation vessels. Untreated cultures and fructose-amended fermenters were used as controls. Bi®dobacterium longum, B. adolescentis and B. angulatum comprised the dominant bi®dobacterial populations throughout the experiment. No major differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…They are used commercially in food products and nutritional supplements. In the intestines of humans, rats, horses, pigs, and chicks, FOS stimulate growth of probiotic bacteria, and some studies have found that they inhibit the growth of pathogenic bacteria such as Salmonella enterica serovar Typhimurium and Escherichia coli (4,7,33,42). Genes involved in the assimilation of FOS by probiotic bacteria, such as lactic acid bacteria, have been identified (3,21,39), but so far they have not been found in pathogenic bacteria.…”
mentioning
confidence: 99%
“…They are used commercially in food products and nutritional supplements. In the intestines of humans, rats, horses, pigs, and chicks, FOS stimulate growth of probiotic bacteria, and some studies have found that they inhibit the growth of pathogenic bacteria such as Salmonella enterica serovar Typhimurium and Escherichia coli (4,7,33,42). Genes involved in the assimilation of FOS by probiotic bacteria, such as lactic acid bacteria, have been identified (3,21,39), but so far they have not been found in pathogenic bacteria.…”
mentioning
confidence: 99%
“…Molecular analyses have been used to assess the effects of NDO on colonic bacterial populations (36,38). These methods allow specific groups of bacteria to be targeted with a high degree of confidence without a need to isolate the organisms from complex communities, and they provide an indication of the relative metabolic potentials of different bacterial groups.…”
mentioning
confidence: 99%
“…The applicant identified one unpublished randomised controlled human intervention study (Drakoularakou et al, claimed to be confidential by the applicant), one unpublished nonhuman study (Searle et al, in press, claimed to be confidential by the applicant), three published in-vitro studies (Sharp et al, 2001;Shoaf et al, 2006;Tzortzis et al, 2005) and one review (Cummings et al, 2004) as being pertinent to the health claim.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%
“…As Bimuno TM was not tested in the in vitro studies by Sharp et al (2001) and by Shoaf et al (2006), the Panel considers that these studies are not pertinent to the health claim.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%